Pemikiran Khaled Abou El-Fadl tentang Otoritarianisme dan Implikasinya terhadap Demokrasi di Indonesia : Penelitian - Muhammad Wildanul Hishom; Mohammad Ainun Rofiq (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article explores the critical thought of Khaled Abou El-Fadl on the relationship between Islam and democracy, focusing on the deconstruction of traditional views and the construction of contemporary interpretations. This research aims to understand how Abou El-Fadl bridges the potential tension between the principle of God's sovereignty in Islam and the sovereignty of the people in democracy, particularly within the Indonesian political context. Through a qualitative literature review of Abou El-Fadl's works and other relevant sources, this article analyzes his intellectual background and biography that shaped his perspective. The discussion includes an in-depth analysis of the concept of democracy, its historical development, and its relevance in Indonesia as a country with a majority Muslim population. The article also examines Abou El-Fadl's arguments regarding the dangers of authoritarianism arising from claims of a singular interpretation of Islamic teachings and the concept of God's sovereignty in the political sphere. Conversely, Abou El-Fadl offers an understanding that the fundamental values of Islam, such as justice, equality, and public welfare, are in line with the principles of democracy.